Parapoxvirus-based therapy eliminates SARS-CoV-2-loaded fine aerosol and blocks viral transmission in hamster models - Cui, Huan; Zhao, Kui; Zhang, Cheng; Lin, Jing; Sun, Shihui; Li, Qi; Du, Le; Zhang, Chunmao; Liu, Juxiang; Gao, Feng; He, Wenqi; Gao, Yuwei; et al. (Frontiers in Microbiology, 2022)
Currently, it is believed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an airborne virus, and virus-containing aerosol particles have been found concurrent with the onset of COVID-19, which may contribute to the noncontact transmission of SARS-CoV-2. Exploring agents to block SARS-CoV-2 transmission is of great importance to prevent the COVID-19 pandemic. In this study, we found that inactivated Parapoxvirus ovis (iORFV), a kind of immunomodulator, could compress the proportion of small particle aerosols exhaled by Syrian golden hamsters. Notably, the concentration of SARS-CoV-2 RNA-containing aerosol particles was significantly reduced by iORFV in the early stages after viral inoculation. Importantly, smaller aerosol particles (less than 4.7 μm) that carry infectious viruses were completely cleared by iORFV. Consistently, iORFV treatment completely blocked viral noncontact (aerosol) transmission. In summary, iORFV may become a repurposed agent for the prevention and control of COVID-19 by affecting viral aerosol exhalation and subsequent viral transmission.